Empty Nest- Mirrored in a growing mind: A Case Report (Journal of Psychiatrists' Association of Nepal, 2014)
We report a case of ‘depression’ with ‘empty nest syndrome’ to highlight the importance of parents for psychic development and of family support for effective management of psychiatric disorder.  A 21-year-old lady presented with history of feeling lonely for 2-years, sadness 1 year; and insomnia and death wishes 3 months. She was staying in her home-town with uncle as both parents went abroad 8 years back. She started missing her parents when she had frequent pain abdomen in last 3 years, she could not succeed in examination and friends were away from her. As her uncle and aunt were also busy preparing for abroad work, she increasingly felt lonely and empty in last 2 years.  With growing loneliness, she felt sad and worried. She reported losing interest, feeling weaker and having ruminating thoughts in last year. In between, she met a boy-friend whom she found supportive; but soon, she started worrying that her parents might not agree to this relationship. In distress, she slashed her wrists. Because of her condition, her parents started visa process, which eased for some time. Despite of visa progress, she could not sleep due to worrying thoughts. She expressed suicidal thoughts many times. And, her relatives brought her for psychiatry consultation, though reluctantly. With diagnosis of ‘depressive episode’, she was put on supervised Mirtazapine and Lorazepam. She was also provided psychotherapy which focused on coping and problem solving strategies addressing her ‘empty nest syndrome’, and family members were advised ‘suicide-precaution’.   DOI: http://dx.doi.org/10.3126/jpan.v2i2.9726 J Psychiatrists’ Association of Nepal Vol.2, No.2, 2013 43-45